Binder-Free Cathode for Thermal Batteries Fabricated Using FeS2 Treated Metal Foam - Kim, In Yea; Woo, Sung Pil; Ko, Jaehwan; Kang, Seung-Ho; Yoon, Young Soo; Cheong, Hae-Won; Lim, Jae-Hong (Frontiers in Chemistry, 2020)
In this study, we fabricated a cathode with lower amounts of additive materials and higher amounts of active materials than those of a conventional cathode. A thermal battery was fabricated using FeS2 treated foam as the cathode frame, and its feasibility was verified. X-ray diffraction, transmission electron microscopy, and scanning electron microscopy were used to analyze the effects of thermal sulfidation temperature (400 and 500 °C) on the structure and surface morphology of the FeS2 foam. The optimal temperature for the fabrication of the FeSx treated foam was determined to be 500 °C. The FeS2 treated foam reduced the interfacial resistance and improved the mechanical strength of the cathode. The discharge capacity of the thermal battery using the FeS2 treated foam was about 1.3 times higher than that of a thermal battery using pure Fe metal foam.